(untitled) (Al-Academy, 2025)
The multiplicity of the circle of coordination in fine art to what is broader than the circle of precise specialization and its artists, which gave many ideas and developments in sculptural works and its achievements in a way that clearly influenced the process of sculpture within the general artistic pattern of the general fine art and not just sculpture. As the artist with precise specialization went beyond With the multiplicity of formats in his works, as he combined drawing and sculpture and combined methods and techniques for the purpose of creating artistic works with multiple formats between drawn sculpture or carved drawing or between painting and sculpture to achieve his desire. Through the above research problem, the researcher decided to pose the following question: What is format? Do they have multiple representations in the products of students at the Institute of Fine Arts?The current research aims to:• Identify the theory of multiple formats in contemporary sculpture.• Revealing the multiple styles and their representations in the sculptural productions of students at the Institute of Fine Arts.Therefore, the researcher adopted the descriptive approach in the analytical method, as it is the most appropriate scientific method to achieve the objectives of the current research. This chapter included several steps and procedures taken by the researcher in order to limit the original research community, as the current research community consists of the products of fifth grade students - Sculpture Department/morning study. (Boys) / Institute of Fine Arts / Ministry of Education - Rusafa The first academic year (2019 AD - 2020 AD) numbered (11) sculptural products. Therefore, it was necessary to choose a purposive sample that consisted of (3) artistic products.To extract the results, the researcher used a set of statistical methods, including Cooper to calculate the percentage of agreement between experts and a single-sample T-test. The most important results are:1-The interest of the theory of multiple formats in post-modern arts due to the convergence of viewpoints among them in terms of thought and orientation. It paid its attention to the art of contemporary sculpture because of its presentation of modern ideas that came as a response to the art of modernity.2- The ability to adapt the texture of the material in any way, using industrial techniques that have brought about a tremendous transformation in the world of contemporary sculptural formation, since the end of the eighties of the last century until now. The most important conclusions are:1- The theory of multiple formats is interested in postmodern arts due to the convergence of viewpoints among them in terms of thought and orientation. It has paid attention to contemporary sculpture art because it presents modern ideas that came as a response to modernist art.2-The ability to adapt the texture of the material in any way, using industrial techniques that have brought about a tremendous transformation in the world of contemporary sculptural formation, since the end of the eighties of the last century until now.